Fetal surgical intervention for myelomeningocele: lessons learned, outcomes, and future implications. (16th December 2019) - Danzer, Enrico; Joyeux, Luc; Flake, Alan W; Deprest, Jan
Abstract : Fetal myelomeningocele (fMMC) closure (spina bifida aperta) has become a care option for patients that meet inclusion criteria, but it is clear that fetal intervention, while improving outcomes, is not a cure. This review will: (1) focus on the rationale for fMMC surgery based on preclinical studies and observations that laid the foundation for human pilot studies and a randomized controlled trial; (2) summarize important clinical outcomes; (3) discuss the feasibility, efficacy, and safety of recent developments in fetal surgical techniques and approaches; and (4) highlight future research directions. Given the increased risk of maternal and fetal morbidity associated with prenatal intervention, accompanied by the increasing number of centres performing interventions worldwide, teams involved in the care of these patients need to proceed with caution to maintain technical expertise, competency, and patient safety. Ongoing assessment of durability of the benefits of fMMC surgery, as well as additional refinement of patient selection criteria and counselling, is needed to further improve outcomes and reduce the risks to the mother and fetus. What this paper adds: High‐quality prospective studies are needed to broaden the indication for fetal surgery in the general myelomeningocele population. Innovative minimally invasive approaches have had promising results, yet lack comprehensive and robust experimental or clinical evaluation. Important information to help families make informed decisions regarding fetal surgery for myelomeningocele is provided. What this paper adds: High‐quality prospective studies are needed to broaden the indication for fetal surgery in the general myelomeningocele population. Innovative minimally invasive approaches have had promising results, yet lack comprehensive and robust experimental or clinical evaluation. Important information to help families make informed decisions regarding fetal surgery for myelomeningocele is provided. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Intervención quirúrgica fetal para mielomeningocele: lecciones aprendidas, resultados e implicaciones futuras: El cierre del mielomeningocele fetal (fMMC) (espina bífida) se ha convertido en una opción de atención para pacientes que cumplen con los criterios de inclusión, pero está claro que la intervención fetal mientras se mejoran los resultados no es una cura. Esta revisión: (1) se centrará en la justificación de la cirugía fMMC basada en estudios preclínicos y observaciones que sentaron las bases para estudios piloto humanos y un ensayo controlado aleatorio; (2) resumir resultados clínicos importantes; (3) discutir la viabilidad, eficacia y seguridad de los desarrollos recientes en técnicas y enfoques de cirugía fetal; y (4) resaltar futuras direcciones de investigación. Dado el mayor riesgo de morbilidad materna y fetal asociada con la intervención prenatal, acompañado por el creciente número de centros que realizan intervenciones en todo el mundo, los equipos involucrados en la atención de estos pacientes deben proceder con precaución para mantener la experiencia técnica, la competencia y la seguridad del paciente. Se necesita una evaluación continua de la durabilidad de los beneficios de la cirugía fMMC, así como un refinamiento adicional de los criterios de selección de pacientes y asesoramiento, para mejorar aún más los resultados y reducir los riesgos para la madre y el feto. Resumo: Intervenção cirúrgica fetal para mielomeningocele: lições aprendidas, resultados e implicações futuras: O fechamento fetal da mielomeningocele (fFMM), ou espinha bífida aberta, se tornou uma opção de cuidado para pacientes que atendem aos critérios de inclusão, mas está claro que, embora melhore os resultados, a intervenção fetal não representa cura. Esta revisão irá: 1) focar nos princípios da cirurgia de fFMM com base em estudos pré‐clínicos e observações que basearam estudos pilotos com humanos e um estudo randomizado controlado; 2) sintetizar resultados clínicos importantes; 3) discutir a viabilidade, eficácia e segurança dos desenvolvimentos recentes em técnicas e abordagens de cirurgia fetal; e 4) destacar direções para futuras pesquisas. Dado o risco aumentado de morbidade maternal e fetal associado com a intervenção pré‐natal, acompanhado pelo aumento no número de centros que realizam a intervenção no mundo, equipes envolvidas no cuidado destes pacientes precisam proceder com cautela para manter a especialidade técnica, competência e segurança dos pacientes. Contínua avaliação da durabilidade dos benefícios da fFMMM, assim como refinamento adicional dos critérios de seleção de pacientes e aconselhamento, são necessários para melhorar os resultados e reduzir os riscos para mãe e feto.